Analysis of the Completeness and Effectiveness of Electronic Inpatient Medical Record at Bandung City Hospital - Afra Nawal Efendy; Erix Gunawan (Greenation Publisher & Yayasan Global Research National, 2025)
Electronic Medical Records (EMR) are a digital documentation system essential for supporting effective and efficient healthcare services. This study aims to analyze the completeness of documentation and the effectiveness of EMR usage in the inpatient ward of RSUD Kota Bandung. A descriptive quantitative method was used with simple random sampling of 92 EMR documents and a questionnaire distributed to 30 healthcare workers. The results showed that the average completeness of EMR documentation was 88%, with the patient identity component achieving 100%, while the initial nursing assessment had the lowest completeness at 77%. The effectiveness assessment produced an average score of 3.97 on a 5-point scale, categorized as effective. The highest-rated indicators were system understanding and target accuracy, while timeliness was the lowest. It can be concluded that the EMR system at RSUD Kota Bandung functions effectively and is relatively complete; however, periodic evaluations, enhanced supervision, and continuous training are needed to optimize its use and improve healthcare service quality.